Sierra Leone beekeepers shine in China - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
A special distinction was awarded to the National Agency for Beekeepers of Sierra Leone at the first International Beeswax Show held recently in Beijing, China, by the Japanese company Cera Rica Noda. The beekeepers had produced an excellent quality...